Dirurnal variability of heat fluxes and heat content at A few locations off central east coast of India During April 1989 (MAUSAM, 1992)
Diurnal variability of surface wind speed, net heat exchange, sea surface temperature, vertical thermal structure and heat content at three locations, viz., station A (17° 59'N, 83° 53.9'E), station B (17° OO'N , 82° 32.1'E) and station C (16° 31..3' N, 82° 21..8'E) off central east coast of India is described making use of the data collected on board R.V. Gaveshani during April 1989 .